Pengaruh Stabilisasi Tanah Lempung dengan Limbah Kaca dan Gipsum terhadap Peningkatan CBR - Muhammad Ikhsan Nurfikri; Dendi Yogaswara (Institut Teknologi Garut, 2026)
Soil is a fundamental element in construction that functions as a structural support and therefore requires adequate characteristics and bearing capacity. Clay soil is known to have low bearing capacity and cohesive properties, so it often requires improvement. This study aims to determine the effect of mixing glass waste powder and gypsum on the California Bearing Ratio (CBR) value of clay soil from Bumi Cempaka Indah, Lebaksari Village, Karangpawitan District, Garut Regency, West Java. This location was selected because it is included in the planned construction of the Gedebage–Tasikmalaya–Cilacap (Getaci) Toll Road, making an assessment of soil bearing capacity necessary as part of infrastructure preparation. The research method uses an experimental approach through testing of physical properties, compaction, and unsoaked CBR on the original soil and soil mixed with glass powder (3%, 6%, and 9%) and a constant gypsum content of 8.5% by soil weight. The classification results show that the original soil belongs to group A-6 according to the AASHTO classification, indicating clay soil of fair to poor quality, and according to the USCS classification it belongs to group CL, or inorganic clay with low to medium plasticity, with an initial CBR value of 5.097%. A mixture of 3% glass powder + 8.5% gypsum increased the CBR to 7.188%. At a mixture of 6% glass powder + 8.5% gypsum, the CBR reached 12.319%, and at a mixture of 9% glass powder + 8.5% gypsum, the highest CBR value of 14.911% was recorded. This represents an increase of 192.54% compared to the original soil CBR value. The results indicate that the combination of glass waste powder and gypsum is effective in improving the bearing capacity of clay soil.